Diversidade de moscas-das-frutas (Diptera: Tephritidae) e seus hospedeiros na região do baixo Jaguaribe, Ceará - Silva, Raimundo Ivan Remígio (Universidade Federal Rural do Semi-Árido, 2014)
Brazil, producing more than 40 million ton of fruits in 2013, is one of the three greatest fruit producer in the world. In spite of the potential, we see some difficulties on the management of the cultures, specially phytosanitary problems. Fruit flies (Diptera: Tephritidae) represent one of the great phytosanitary for fruit growing due to damage on the fruits and quarantine restrictions, whose loss is equivalent one billion dollars per year. Thus, this work aimed to know the species of fruit flies through some traps, as well as accomplishing a prospection of host vegetable species on the region Baixo Jaguaribe, Ceará. The study was accomplished from 2010 to 2013, being divided in two stages: capture of flies, accomplished through McPhail traps Hydrolysed Maize Protein at 5% and periodical collections of fruits form cultivated or wild species. Identification of fruit flies species was accomplished in Applied Entomology Laboratory of UFERSA, considering female morphological characters. The number of fruit flies captured with traps was 6.350 and 9.626 were captured using fruit collection, being collected 64 vegetable species, from which 17 were infected by Ceratitis capitata and/or Anastrepha spp. C. capitata species represent approximately 75% of collected species; six species Anastrepha: Anastrepha sororcula, A. zenildae, A. obliqua, A. dissimilis, A. pickeli and A. alveata, being the last one registered for the first time in the state of Ceará. A. sororcula represents 72% of females and is associated specially to guava. A. zenildae is associated to guava, juazeiro, castanhola and murici and A. obliqua is associated to cajarana. The greatest infestation index for C. capitata were observed in castanhola, sapoti, seriguela, pitanga, acerola, guava and murici and for Anastrepha spp., murici, guava and juazeiro
Fruit flies -(Diptera: Tephritidae) end their hosts in the region of Low Jaguaribe, Ceará
Keywords: The fruit flies; Species vegetables - infestation; Fruit growing - monitoring; Phytosanitary problems - fruit growing; Moscas-das-frutas; Espécies vegetais - índices de infestação; Fruticultura monitoramento; Problemas fitossanitários fruticultura; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA